Mutu Pendidikan Sekolah Dasar Ditinjau dari Teknologi Informasi dan Manajemen Berbasis Sekolah - Nini Arianti; Syarwani Ahmad; Rohana Rohana (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
The purpose of this study was to determine the effect of information technology and school-based management on the quality of education in public elementary schools in Sematang Borang sub-district, Palembang. This research is included in the type of expost facto research. The population and sample in this study amounted to 111 people. Data collection techniques using questionnaires, questionnaires and documentation. Data analysis techniques used normality test, linearity test, multicollinearity test, heteroscedasticity test, simple correlation analysis, multiple correlation analysis, simple regression analysis, t test and F test. The results of this study are information technology and school-based management have a joint positive effect on the quality of education in public elementary schools in Sematang Borang sub-district, things that affect the quality of education of a school, namely, increasing the quality and quantity of services independently, timeliness or school discipline, responsibility, ability and reliability in utilizing information technology and being able to provide services according to community needs. In conclusion, there is a positive and significant influence between information technology variables and school-based management on the quality of education Keywords: Education quality, Information technology, School-based management.